Implementasi Ekonomi Hijau untuk Peningkatan Daya Saing dan Keberlanjutan: Pendampingan pada Pokmas Al-Fatihah Farm, Desa Jelbuk - Khanifatul Khusna; Hari Sukarno; Salma Fauziyyah; Ro'isyatul Mu'amanah; Beny Firmansyah (Yayasan Literasi Sains Indonesia, 2025)
This community service initiative was driven by the weak governance of micro-enterprises in rural areas, which hold significant economic potential but remain underutilized both managerially and ecologically. Pokmas Al-Fatihah Farm in Jelbuk Village, Jember Regency, serves as a case in point, focusing on the production of cassava-based plate chips. Despite the promising market opportunities, the group faced persistent challenges related to business management, pricing strategies, and production efficiency. By applying the Asset-Based Community Development (ABCD) approach, the program sought to embed green economy principles into the cooperative’s operations. The activities included training on simple financial record-keeping, the adoption of environmentally friendly appropriate technologies, and counseling on business efficiency and sustainability. The outcomes demonstrated a notable enhancement in members’ managerial capabilities, more efficient use of raw materials and energy, as well as the cultivation of ecological awareness in enterprise management. Ultimately, this program highlights a model of village-level economic empowerment that is both adaptive to environmental challenges and aligned with sustainable development goals.